227k views
1 vote
Solve for n in the literal equation a(n − 5) + 6 = bn.

User RetnuH
by
5.3k points

2 Answers

3 votes

Answer:


a(n - 5) + 6 = bn \\ an - 5a + 6 = bn \\ an - bn = 5a - 6 \\ n(a - b) = 5a - 6 \\ n = (5a - 6)/(a - b) \\ thank \: you

User Tdimeco
by
5.9k points
5 votes

Answer:

(6-5a)/(b-a) = n

Explanation:

a(n − 5) + 6 = bn

Distribute

an -5a +6 = bn

Subtract an from each side

an -5a+6 -an = bn-an

6-5a = bn-an

Factor out n

6-5a = n(b-a)

Divide each side by (b-a)

(6-5a)/(b-a) = n

User Kennen
by
5.7k points